On Convergence of Fixed Points in G-Complete Fuzzy Metric Spaces - Dong Qiu; Shuai Deng (Journal of Function Spaces)
We provide some results on the convergence of the sequence of fixed points for some different sequences of contraction mappings or fuzzy metrics in G-complete fuzzy metric spaces with the H-type t-norms. We improve the corresponding conclusions in the literature.